Financial Technology: Pinjaman Online, Ya Atau Tidak - Sinaga, Hommy Dorthy Ellyany; Irawati, Novica; Kurniawan, Edi (LPPM STIKOM Tunas Bangsa, 2019)
The objective of community service which given to the Dharma Wanita Persatuan of Haji Abdul Manan Simatupang Regional Hospital is to sosialize the financial technology focusing on uncover the online lending risk. This community service is aimed to bring more knowledge about online lending that will help the member of Dharma Wanita to solve the unknown information of the online lending, so they can be smart enough in making decision to choose and taking the online lending. The service was held for one day at 21st of August 2019, in Medical Committee Room at Haji Abdul Manan Simatupang Regional Hospital. The method used was giving speech dan interactive discussion. All attendance were giving positif response about this sosialization service activity.